Medical Personnel Injuries: The Problem and the Solution, An Emphasis on Sonographer Workplace Injuries - Speir, Shelby (URJ-UCCS: Undergraduate Research Journal at UCCS, 2023)
Injuries in the workplace are a common and troublesome fact of life for employees as well as employers. This paper focuses on injuries in the medical field and, more specifically, work-related injuries among ultrasound technologists or sonographers. By investigating techniques, procedures, and possibly equipment to aid sonographers in their day-to-day tasks, these acute injuries and long-term disabilities may be prevented. Help comes in many different forms, from general awareness, intelligent ordering, the use of exoskeletons, and utilizing technology from robotic surgery. By bringing to light the trials and disregard ultrasound technologists encounter, we may be able to mitigate injuries and alleviate the financial burden on the hospital system and the employee. We may also reduce the emotional and mental strain on ultrasound technologists so our frontline caregivers can focus on providing patients the best care possible while remaining physically able to remain in the field they love.